Real Exchange Rate Misalignment : A Panel Co-Integration and Common Factor Analysis - Yehoue, Etienne (IMF Working Papers; Working Paper ;, 2005)
We combine some newly developed panel co-integration techniques and common factor analysis to analyze the behavior of the real exchange rate (RER) in a sample of 64 developing countries. We study the dynamic of the RER with its economic fundamentals: productivity, the terms of trade, openness, and government spending. We derive a number of common factors that explain the dynamic of the RER in our sample. We find that while some fundamentals such as productivity, terms of trade, and openness are strongly related to these common factors in low-income countries, no such link is found for the middle-income countries. We also derive the misalignment indices, which seem to reproduce recent episodes of overvaluation and undervaluation in a number of countries.